2015
DOI: 10.1136/jmedgenet-2015-103471
|View full text |Cite
|
Sign up to set email alerts
|

Antiproteinuric therapy and Fabry nephropathy: factors associated with preserved kidney function during agalsidase-beta therapy

Abstract: BackgroundNephropathy is an important feature of classical Fabry disease, which results in alpha-galactosidase A deficiency and cellular globotriaosylceramide accumulation. We report the safety and efficacy of antiproteinuric therapy with ACE inhibitors or angiotensin II receptor blockers (ARBs) in a study of classical Fabry patients receiving recombinant agalsidase-beta therapy.Methods and designThe goal was maintenance of urine protein to creatinine ratio (UPCR) <0.5 g/g or a 50% reduction in baseline UPCR f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 30 publications
(43 reference statements)
1
58
0
1
Order By: Relevance
“…A recent study by Germain and colleagues showed that less affected individuals with a better preserved kidney function at baseline benefited from ERT, experiencing better renal and cardiovascular outcomes during the observational period [36]. Moreover, in male FD patients, enhanced therapeutic outcomes may occur if we increase the ERT dose [35, 37, 38], or frequency of infusions [39], in combination with intensified additional medication such as ARBs and ACE inhibitors [16]. In patients with amenable mutations, pharmacological chaperones have been shown as a useful therapeutic alternative [40, 41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Germain and colleagues showed that less affected individuals with a better preserved kidney function at baseline benefited from ERT, experiencing better renal and cardiovascular outcomes during the observational period [36]. Moreover, in male FD patients, enhanced therapeutic outcomes may occur if we increase the ERT dose [35, 37, 38], or frequency of infusions [39], in combination with intensified additional medication such as ARBs and ACE inhibitors [16]. In patients with amenable mutations, pharmacological chaperones have been shown as a useful therapeutic alternative [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Although NLME is frequently applied in clinical drug development, to our knowledge, it is the first time that this method was utilized to characterize progression of the Fabry nephropathy over time, quantify effects of ERT, as well as key covariates on kidney function. Previous studies used linear multivariate regression models for outcome analyses as a common statistical tool [16, 31, 32]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that proteinuria in most classical FD patients was controlled, but that kidney function was not preserved in patients who did not achieve the urine protein to creatinine ratio (UPCR) treatment goal of 0.5 g/g. Kidney function was preserved in a minority of patients who started ERT at a younger age, and who maintained a UPCR < 0.5 g/g with antiproteinuric therapy [86]. There is some evidence supporting that the use of amiloride, a drug with proven effects in podocyte stabilization and proteinuria actions at the distal convoluted tubule, can decrease protein excretion in FD patients [87], but further research is needed.…”
Section: Treatment Of Fabry Nephropathymentioning
confidence: 99%
“…When urine protein excretion was controlled to a target of ≤0.5 g/day by carefully titrating ACEI and ARB doses in these adult Fabry patients who were also treated with agalsidase beta at 1 mg/kg every other week (EOW), the rate of loss of eGFR was not significantly different than zero [85]. A few years later, Warnock et al [86] conducted a prospective observational study that examined the safety and efficacy of controlling proteinuria with ACEI or ARB therapy in FD patients who were receiving ERT with agalsidase beta. Results showed that proteinuria in most classical FD patients was controlled, but that kidney function was not preserved in patients who did not achieve the urine protein to creatinine ratio (UPCR) treatment goal of 0.5 g/g.…”
Section: Treatment Of Fabry Nephropathymentioning
confidence: 99%